First record of the Lessepsian nereidid Pseudonereis anomala Gravier, 1899 (Annelida: Nereididae) in the western Mediterranean Sea - Kurt, Güley; Rezzag-Mahcene, Hiba; Kuş, Sevgi; Daas, Tarek; Villalobos-Guerrero, Tulio F. (Cahiers de Biologie Marine, 2021)
This is the first record of the Lessepsian polychaete Pseudonereis anomala Gravier, 1899 in the western Mediterranean Sea, specifically in Skikda Bay, Algeria. The species was collected among rocks covered by algae at 0.5 m depth. A characterization of the species, as well as some ecological and distributional aspects are provided. [ Premier signalement du néréide Pseudonereis anomala Gravier, 1899 (Annelida : Nereididae) en Méditerranée occidentale. Il s'agit d'une premiere apparition de Pseudonereis anomala Gravier, 1899, polychète lessepsien, en Méditerranée occidentale, en particulier dans la baie de Skikda, Algérie. L'espèce a été recueillie sur des roches recouvertes d'algues à 0,5 m de profondeur. Une caractérisation de l'espèce, ainsi que certains aspects écologiques et de distribution sont fournis.]
World Polychaeta Database (WPolyDb). DOI is not activated as at 06/04/2021